Evaluation of serological assays to monitor antibody responses to single-dose HPV vaccines. Issue 38 (27th August 2020) - Tsang, Sabrina H.; Basu, Partha; Bender, Noemi; Herrero, Rolando; Kemp, Troy J.; Kreimer, Aimée R.; Müller, Martin; Panicker, Gitika; Pawlita, Michael; Pinto, Ligia A.; Sampson, Joshua N.; Sankaranarayanan, Rengaswamy; et al.
Abstract: Introduction: Whether existing serological assays are sufficiently robust to measure the lower antibody levels expected following single-dose HPV vaccination is unknown. Methods: We evaluated seven assays measuring HPV-16/18 immunological responses overall and by number of doses in 530 serum samples from participants receiving varying doses of Cervarix or Gardasil up to 36-months post-vaccination. Serum was evaluated by simplex (HPV-16 ELISA, HPV-18 ELISA), multiplex (LIA-4, VLP-MIA, M9ELISA, GST-L1), and high-throughput pseudovirion-based neutralization assays (HT-PBNA), and results were compared to the gold standard HPV-16/18 secreted alkaline phosphatase neutralization assay (SEAP-NA). Reproducibility was assessed by the coefficient of variation (CV) and intraclass correlation coefficient (ICC). Percent agreement, Pearson correlation, and weighted-kappa were used to assess validity. Determinants of seronegativity were evaluated by chi-squared test. Results: HPV-16: Seropositivity range was 97.1–99.5% for single dose and 98.8–99.8% overall. CV range was 4.0–18.0% for single dose and 2.9–19.5% overall. ICC range was 0.77–0.99 for single dose and 0.74–0.99 overall. Correlation with SEAP-NA range was 0.43–0.85 for single dose and 0.51–0.90 overall. Weighted-kappa range was 0.34–0.82 for single dose and 0.45–0.84 overall. HPV-18: Seropositivity range was 63.9–94.7% for single dose and 86.2–97.9% overall. CV range was 8.1–18.2% for single dose and 4.6–18.6% overall. ICC range was 0.75–0.99 for single dose and 0.83–0.99 overall. Correlation with SEAP-NA range was 0.31–0.99 for single dose and 0.27–0.96 overall. Weighted-kappa range was 0.35–0.83 for single dose and 0.45–0.84 overall. HPV-16 seronegativity was <5% for all assays. HPV-18 seronegativity range was 5.5–17.3%. For LIA-4 and GST-L1 where the proportion of seronegativity was >10%, the strongest correlates of seronegativity were receiving a single vaccine dose and receiving Gardasil. Conclusions: These results support the utility of existing serological assays to monitor antibody responses following single-dose HPV vaccination.